Application of Analysis of the Statistical Data to Formation of the State Order for the Teacher Training - Januškevičius, Romanas; Pumputis, Dalius (Lithuanian Journal of Statistics, 2013)
As a source of socially significant information, statistics plays an important role in the modern society. Inability to value and understand this role can be referred to as statistical illiteracy, which can cause some negative tendencies in the development of social processes. In such activities, a disregard of statistical data analysis can lead to an inefficient use of public funds. The paper deals with the illustration of the application of statistical regularities in such an important area of education as the formation of the state order in the process of teacher training. However, the main purpose of this paper is not only to show that the reduced number of study vouchers is not proportional to the reduced number of teachers working at secondary schools but also to emphasise that the structure of the state order for teacher training is totally unbalanced, and, in fact, is being formed without training of a young generation of mathematics, informatics, biology, geography, chemistry, physics and astronomy teachers.
Keywords: statistical data analysis; application of statistical regularities; statistical literacy; study voucher